Specifying Influences that Mediate Trust in Human-Robot Interaction. (September 2016) - Volante, W.G.; Sanders, T.; Dodge, D.; Yerdon, V.A.; Hancock, P.A.
In this work we investigate the effects of robot appearance and reliability on a user's trust levels through an experiment where participants reacted to three different robot forms that either behaved reliably or unreliably during a series of experimental trials. A final trial was implemented to evaluate use choice by allowing participants to choose their preferred robot and complete an additional trial with that robot. Results from this pilot experimentation indicated differences based on the reliability of the robot, as well as whether the participant chose to interact with the robot.